Community Natural Resource Management in the Highlands of Ethiopia - Gebremedhin, Berhanu; Pender, John L.; Tesfay, Girmay (International Food Policy Research Institute, 2006)
Common property resources1 are important sources of timber, fuelwood, and grazing land in developing countries. When community members have unrestricted access to the resource, or when use regulations are ineffective, these resources are exploited on a first-come, first-served basis. Each individual user of the resource will tend to continue to use the resource until her average revenue is equal to the marginal cost of using the resource (Gordon 1954). In the presence of externalities, social marginal cost exceeds private marginal cost, and common property resources can still be degraded if an individual equates her marginal cost with her marginal benefit of utilizing the resource. These conditions lead to overexploitation of the resource and the dissipation of the scarcity rent.